PENGGUNAAN KALIMAT EFEKTIF DALAM TEKS DESKRIPSI SISWA KELAS VII SMP MAHAPUTRA TELLO MAKASSAR: The Use of Effective Sentences in Descriptive Texts by Students In Grade VII of Mahaputra Tello Junior High School In Makassar - Aqiqah Am, Andi; Azis; Wijayanti, Tuti (Journal of Applied Linguistics and Literature, 2025)
This study aims to describe various forms of errors in sentence usage by seventh-grade students at Mahaputra Junior High School when writing descriptive texts, with a focus on sentence effectiveness. This study uses a descriptive qualitative method, in which data is collected through students' descriptive texts and then analysed to identify errors. The study data consisted of 11 students' descriptive texts, which were presented in tabular form with students coded using letters of the alphabet, while errors were marked with numbers. The results of the analysis showed that the use of effective sentences in students' descriptive texts did not meet the requirements for effective sentences as a whole. From a total of 11 texts, various errors were found that indicated a lack of understanding among students regarding the aspects of sentence effectiveness. These findings indicate that there is still much room for improvement in terms of composing sentences that are more effective and in accordance with the applicable rules.